A scoping review of psychosocial interventions to enhance the relationship of couples living with dementia. (July 2023) - Gilbert, Emma; Villa, Darrelle; Riley, Gerard A
When dealing with the challenges of dementia, spousal relationships have a central role to play in outcomes such as quality of care and emotional wellbeing. Dementia places strain on these relationships and so it is important to develop interventions to support them. This review maps out what interventions have been employed in this context. Searches of PsycInfo, PsycArticles, CINAHL, Embase, MEDLINE, and Web of Science were conducted to find studies describing interventions that aimed to improve some aspect of the relationship. Thirty-four studies were identified. A wide range and diversity of interventions were described, including life review, psychotherapy and ones focused on communication or creative activity. Reported benefits included meaningful interaction, emotional connection, reduced conflict and negativity, an increase in mutual support, and greater equality in the relationship. However, these can only be considered as potential rather than proven benefits because of the lack of methodological rigour of most of the studies. Future research on this topic would benefit from a closer links with research on the impact that dementia can have on spousal relationships, and from the use of stronger methodology.